Integrating Local Wisdom in Elementary School to Strengthen Cultural Identity in the Digital Era - Ilham Wahyudi; Herwin Herwin; Wuri Wuryandani; Candra Tri Utami (Yayasan Keluarga Guru Mandiri, 2025)
Multicultural Indonesia has local wisdom as a marker of national identity, but rapid digitalization—accelerated by the COVID-19 pandemic—has changed students' perceptions, rendering cultural values obsolete. This study describes a strategy for cultural preservation by integrating local wisdom into intra- and extracurricular activities in elementary schools. A qualitative design was implemented through observation, semi-structured interviews, and document analysis. Participants (students, teachers, and principals) were purposively selected in educational units that instill cultural values. Data were analyzed using the Miles, Huberman, and Saldana interactive model (reduction, presentation, and verification) and validated through the triangulation of sources and techniques. These local wisdom-based activities foster students' cultural identity while enhancing cognitive, affective, and psychomotor domains. The implications of these findings include the need for ongoing policy support, targeted teacher training, and the judicious use of technology to maintain cultural content in digital classrooms. The results indicate that schools function as agents of cultural transmission, as local content is integrated into Javanese Language, Fine Arts, and Civic Education subjects. At the same time, Pencak Silat and Karawitan expand their practices into extracurricular areas. These findings underscore the importance of revitalizing local wisdom as a foundation for character education in today's globalized world.